Prevalence of sedative drug use and associated risk factors among medical students in Karachi, Pakistan - Mubashir Zafar; Tafazzul Hyder Zaidi; Hameed Mumtaz Durrani; Farooq Yousuf; Muhammad Nalwala; Ebad Ur Rehman; Muhammad Burhan (Discover Public Health)
Abstract Background Stress is widely recognized as a significant issue among medical students worldwide. This stress can disrupt their sleep, potentially leading them to use sedative drugs. Due to the lack of data on this issue in Karachi, this study aims to examine the prevalence of sedative drug use and associated risk factors among medical students in Karachi, Pakistan. Method It was a cross sectional study and total of 336 medical students were enrolled in the study through stratified random sampling method; validated questionnaire was used to for data collection. Binary logistic regression analysis was used to determine the association with sedative drug used and its risk factors. P value < 0.05 was considered significant. Result This study found that 11% of students use sedative drugs. Students who live in hostels are more likely to use these drugs (19%) compared to students who commute from home (8.1%). The most common sedative drug used was benzodiazepine, accounting for about 35% of all sedative use. The researchers looked at several factors to see what might influence sedative drug use: Having a sleep disorder was the only factor significant association with sedative drug use. students with diagnosed sleep disorders were about 2.5 times more likely to use sedative drugs. Conclusion Medical students used sedative drugs and common risk factor was sleep disorder. These findings underscore the need for targeted interventions to address stress and promote healthier coping strategies among students.